Preparation of hybrid chitosan membranes by selective laser sintering for adsorption and catalysis. (5th July 2019) - Sun, Pengbo; Zhang, Lijing; Tao, Shengyang
Abstract: The processing method of natural polymers is one of the critical factors affecting their application. As commonly used biomass, chitosan was usually shaped by a wet chemical method which dissolves chitosan in a solvent and then fabricated into the membrane, fiber or other forms. This process often needs a large number of solvents and acids, which are harmful to the environment. In this paper, we mixed chitosan powder and thermoplastic polyurethane to form membrane by selective laser sintering. This method has advantages of simple operation, fast membrane formation, and low preparation cost. No solvents were applied in the whole progress. The hybrid membrane had an adsorption performance for heavy metal ions, the maximum adsorption capacities to Cu(II) and Pb(II) reached 19.6 mg g −1 and 30.4 mg g −1, respectively. Palladium ions could also be adsorbed by the membrane to form palladium-loaded composite materials, which could be used as a catalyst for reducing p-nitrophenol, and the conversion rate could reach 96% in 20 min. Graphical abstract: Unlabelled Image Highlights: Chitosan and thermoplastic polyurethane composite membranes were prepared by laser sintering technique. The preparation method was simple, and no solvent was used in the preparation process. The composite membrane has the function of adsorbing heavy metal ions. It can be used as a catalyst for reducing p-nitrophenol and has good stability.